Sugar sensing by ChREBP/Mondo-Mlx — new insight into downstream regulatory networks and integration of nutrient-derived signals. (April 2018) - Havula, Essi; Hietakangas, Ville
Highlights: ChREBP/Mondo-Mlx is an intracellular sugar sensor conserved in animals. ChREBP/Mondo-Mlx integrates multiple nutrient-derived inputs. ChREBP/Mondo-Mlx controls the expression of hormones and transcription factors. Abstract : Animals regulate their physiology with respect to nutrient status, which requires nutrient sensing pathways. Simple carbohydrates, sugars, are sensed by the basic-helix–loop–helix leucine zipper transcription factors ChREBP/Mondo, together with their heterodimerization partner Mlx, which are well-established activators of sugar-induced lipogenesis. Loss of ChREBP/Mondo-Mlx in mouse and Drosophila leads to sugar intolerance, that is, inability to survive on sugar containing diet. Recent evidence has revealed that ChREBP/Mondo-Mlx responds to sugar and fatty acid-derived metabolites through several mechanisms and cross-connects with other nutrient sensing pathways. ChREBP/Mondo-Mlx controls several downstream transcription factors and hormones, which mediate not only readjustment of metabolic pathways, but also control feeding behavior, intestinal digestion, and circadian rhythm.